Study of Preferential Weld Corrosion in Carbon Dioxide Environment with Flowing Conditions - Ghazali, Nur Ajwa (IRC, 2021)
Preferential weld corrosionkis a form of galvanic corrosion that occursjin the carbon steel oil & gas pipelines due to the presence of CO2 and the flowing conditions. Preferential weld corrosions occur at the welded joints of the pipelines that consists of